Hubungan Gaya Hidup dengan Kejadian Stroke - Hartaty Hartaty; Abdul Haris (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background; risky behavior leads to unbalanced consumption and smoking habits, drinking alcoholic beverages, and lack of exercise. Method; a case-control study with a retrospective approach. The number of respondents 30 people obtained by purposive sampling. Data analysis using univariate and bivariate. Result; statistical test showed smoking (p = 0.001), alcohol (p = 0.002), diet (p = 0.000), exercise (p = 0.000) had a relationship with the incidence of stroke. Conclusion; In stroke patients who do not regularly control treatment, the incidence of stroke will increase compared to those who regularly control medication. Non-adherence to therapy programs is a major problem in stroke survivors